Sintesis Tasawuf Said Aqil Siradj Sebagai Strategi Pembentukan Insan Kamil - Mustika Rahmawati; Soleh Ibrahim; M. Fauzi Al Fariz; David Febrianto; Dzaki Hasbil Azkiya (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This research examines the concept of humanistic Sufism formulated by Said Aqil Siradj and its relevance to the development of al-insan al-kamil within the framework of integrative Islamic education. The study originates from concerns over moral degradation and the dominance of intellectual development in modern education, which often neglects emotional, ethical, and spiritual dimensions. The purpose of this research is to explore the philosophical foundations, values, and educational implications of Said Aqil’s Sufi thought as a transformative model for character building. This study employs a qualitative library research design using a conceptual-sufistic approach and thematic analysis to examine academic literature related to Sufism, spirituality, humanism, and Islamic education. Data were collected through documentation and analyzed to identify core concepts and pedagogical implications. The findings indicate that Said Aqil Siradj’s Sufism integrates vertical devotion to God and horizontal responsibility toward humanity. Elements such as tazkiyat an-nafs, ihsan, compassion, and inclusive ethics serve as strategic foundations for shaping holistic human character.